2013
DOI: 10.1038/hr.2013.130
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure control and management of very elderly patients with hypertension in primary care settings in Spain

Abstract: This study aimed to determine the clinical profile, blood pressure (BP) control rates, therapeutic management and physicians' therapeutic behavior regarding very elderly hypertensive patients. A total of 1540 hypertensive patients 80 years old on antihypertensive therapy and receiving care in primary care settings in Spain were included in this cross-sectional study. The mean patient age was 83.4±3.1 years, 61.9% of patients were women and 49.3% of patients had cardiovascular disease. Of the patients, 27.7% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
2
10
0
1
Order By: Relevance
“…In the present study, women tended to have higher recorded BP values than men, irrespective of treatment status. A similar pattern of sex disparity in BP measurement was noted in a Spanish study [37]. This finding appears to support the view that men who reach older ages may in some respects be healthier than their female counterparts [38,39].…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, women tended to have higher recorded BP values than men, irrespective of treatment status. A similar pattern of sex disparity in BP measurement was noted in a Spanish study [37]. This finding appears to support the view that men who reach older ages may in some respects be healthier than their female counterparts [38,39].…”
Section: Discussionsupporting
confidence: 85%
“…33 However, in Spain and the United States, physicians failed to increase medications in most uncontrolled hypertensive patients, especially in the elderly. 34,35 Reluctance to initiate combination therapy in older patients was often because of safety concerns such as orthostatic hypotension. [4][5][6][7] Also, as reported in the United States, 32 we found that the proportion of treated uncontrolled patients taking 1 to 2 medications (a proxy for treatment inertia in our study) fell from 89.3% in 2000 to 2001to 81.9% in 2008 to 2010, and the proportion on ≥3 medications (a proxy for apparent treatment-resistant hypertension) rose from 10.6% in 2000 to 18.1% in 2010 (data not presented).…”
Section: Explanations For Changes In Hypertension Controlmentioning
confidence: 99%
“…La literatura revisada plantea que hasta los 50 años los varones aportan un mayor número de casos de HTA, lo que se invierte al pasar esta edad, ya que las mujeres después de la quinta década de la vida inician la menopausia, y debido a la disminución de las hormonas sexuales femeninas quedan más expuestas a sufrir esta enfermedad [12,13].…”
Section: Discussionunclassified